Daya Tahan dan Eksistensi Pesantren Di Era 4.0 - Manan, Muhamad Abdul (Jurnal Pendidikan Islam Indonesia, 2019)
Pesantren as one of the religious education institutions that are the womb of the prospective Muslim scholars, they also have a mandate to carry out educational missions based on Article 1 (1) of Law No. 20 of 2003 namely developing the potential of students to have religious spiritual power, self-control, personality, intelligence, noble character and skills needed by him, society, nation, and state. Era of Industrial Revolution 4.0 (here in after: Era 4.0) has an unimportant impact. It affects all aspects of human life. Included in this case is education. This era is characterized by the increasingly central role of cyber technology in human life. So do not be surprised if in the world of education the term "Education 4.0" appears. Availability of various information is born from the 4.0 digital revolution makes everyone able to access knowledge without being limited by space and time, therefore the pesantren curriculum continues to be encouraged to be contextual to the needs of the times, but on the other hand the pesantren is still able to maintain its identity as guardian of tradition. Efforts that can be developed in Islamic boarding schools in the era of 4.0 include building digital literacy in Islamic boarding schools and creating Islamic study channels.